Fasting Indicators of Insulin Sensitivity: Effects of Ethnicity and Pubertal Status - Adam, Tanja C. (American Diabetes Association, 2011)
OBJECTIVE: To examine the relationship of fasting indicators of insulin sensitivity with a more invasive measure of insulin sensitivity (frequently sampled intravenous glucose tolerance test [FSIVGTT]) and the effect of Tanner stage and ethnicity on that relationship. RESEARCH DESIGN AND METHODS: Data were analyzed from 149 overweight girls (97 Hispanic and 52 African American) who were either in the early stages of maturation defined by Tanner stages 1 or 2 (52 Hispanic and 18 African American) or in the later stages of maturation defined by Tanner stages 4 and 5 (45 Hispanic and 34 African American). Fasting indicators of insulin sensitivity (IS) included fasting insulin and glucose and the homeostasis model assessment of insulin resistance (HOMA-IR). IS was derived from an FSIVGTT with minimal modeling. RESULTS: In Tanner stages 1 and 2, all fasting indicators were significantly associated with IS: (fasting insulin: r = −0.67, P < 0.01; HOMA: r = −0.66, P < 0.01) with no significant influence of ethnicity on these relationships. In Tanner stages 4 and 5, however, all fasting indicators were associated with IS in African American girls (fasting insulin: r = −0.55, P < 0.01; HOMA: r = −0.47, P < 0.01), but none of the indicators were significantly associated with IS in Hispanic girls. CONCLUSIONS: Fasting indicators were reflective of IS for girls in Tanner stages 1 and 2, regardless of ethnicity and may provide a clinical measure of future risk for type 2 diabetes. In the latter stages of maturation, however, more invasive measures are warranted to adequately determine IS in clinical practice.